Addressing Vulvovaginal Atrophy (VVA)/Genitourinary Syndrome of Menopause (GSM) for Healthy Aging in Women - Nappi, Rossella E.; Martini, Ellis; Cucinella, Laura; Martella, Silvia; Tiranini, Lara; Inzoli, Alessandra; Brambilla, Emanuela; Bosoni, David; Cassani, Chiara; Gardella, Barbara (Frontiers in Endocrinology, 2019)
Vaginal health is an essential component of active and healthy aging in women at midlife and beyond. As a consequence of hormonal deprivation and senescence, the anatomy and function of urogenital tissues are significantly affected and vulvovaginal atrophy (VVA) may occur. In a high proportion of postmenopausal women, progressive and chronic VVA symptoms have a strong impact on sexual function and quality of life. The new definition of genitourinary syndrome of menopause (GSM) comprises genital symptoms (dryness, burning, itching, irritation, bleeding), sexual symptoms (dyspareunia and other sexual dysfunctions) and urinary symptoms (dysuria, frequency, urgency, recurrent urinary infections). Age, sexual activity and partnership status influence the clinical relevance of VVA/GSM symptoms and the attitude of women to seek active treatment over time. Psychosocial factors play a critical role in sexual functioning of elderly women, but the integrity of the urogenital system is as well important affecting many aspect of postmenopausal women’s health, including sexual function. Several international surveys have extensively documented the need to improve VVA/GSM management because of the strong impact on women’s daily life and on couple’s intimacy. Health care providers (HCPs) need to be proactive in the early recognition of VVA/GSM in order to preserve urogenital and sexual longevity. The clinical diagnosis is based on genital examination to identify objective signs and on the use of subjective scales to rate most bothersome symptoms. Recent studies point to the importance of addressing VVA/GSM as a potential early marker of poor general health in analogy with vasomotor symptoms. Therefore, a standard of VVA/GSM care in elderly women is desirable to enhance physical, emotional and mental well-being.